Age‑performance and intensity of grooming behavior toward Varroa destructor in resistant and susceptible Apis mellifera colonies - Russo, Romina Maria; Landi, Lucas; Muntaabski, Irina; Liendo, María Clara; Pietronave, Hernan Pablo; Merke, Julieta; Rodriguez, Graciela Adriana; Palacio, María Alejandra; Basilio, Alicia Mabel; Lanzavecchia, Silvia Beatriz; Scannapieco, Alejandra Carla (Springer, 2024)
Grooming behavior confers resistance to honey bees against Varroa destructor, being of interest to social immunity studies and breeding programs. The objective of this study was to characterize at the individual level the grooming behavior of mite-resistant (R) and susceptible (S) A. mellifera stocks from Argentina. Assays were performed in experimental arenas by applying two treatments to nurse bees: (1) placing a V. destructor mite on the bee’s thorax and (2) touching the bee with a paintbrush. Grooming reactions were recorded on bees from both stocks at the ages of 6, 10, and 14 days after emergence. R bees exhibited lower time of first response against the mite, performed more cleaning attempts, and used all their legs with a higher probability compared to S bees. The same pattern was evident when younger and older bees from the R stock were compared. The results demonstrate that bee age and genetic origin are critical factors of grooming behavior in honey bees.